The Role of Nucleotides and Purinergic Signaling in Apoptotic Cell Clearance – Implications for Chronic Inflammatory Diseases - Chen, Jin; Zhao, Yi; Liu, Yi (Frontiers in Immunology, 2014)
Billions of cells undergo apoptosis every day in healthy individuals. A prompt removal of dying cells prevents the release of pro-inflammatory intracellular content and progress to secondary necrosis. Thus, inappropriate clearance of apoptotic cells provokes autoimmunity and has been associated with many chronic inflammatory diseases. Recent studies have suggested that extracellular adenosine 5’-triphosphate (ATP) and related nucleotides play an important role in the apoptotic clearance process. Here, we review the current understanding of nucleotides and purinergic receptors in apoptotic cell clearance and the potential therapeutic targets of purinergic receptor subtypes in inflammatory conditions.